Antiretroviral Pre-Exposure Prophylaxis Awareness, Experience and Acceptance among Men who have Sex with Men in Southwest Switzerland - K.E.A. Darling; O. Clerc; A. Calmy; E. Boffi El Amari; M. Cavassini (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Objectives Antiretroviral pre-exposure prophylaxis (PrEP) against HIV acquisition has been shown to be safe and effective in populations at risk of HIV acquisition. We examined PrEP awareness, experience and acceptance among men who have sex with men (MSM) in southwest Switzerland. Methods Between 1st June 2011 and 31st August 2012, individuals attending 1) MSM screening clinics (Checkpoint Geneva) and 2) meeting areas were invited to complete an anonymous questionnaire covering sexual practices and PrEP awareness, experience and interest in participating in future PrEP trials. Results Of 918 men approached, 654 (71%) agreed to participate, the majority (536/654, 82%) enrolled via Checkpoint. Most participants (512/654, 78%) were homosexual; 21/654 (3.2%) disclosed being HIV-positive; 140/654 (21%) had unknown HIV status. Unprotected anal intercourse (UAI) with a partner of different or unknown HIV status (non-serosorting) was practised by 49% of participants during the preceding year, more by participants of positive / unknown HIV status than by those negative / undisclosed status (68% vs 43%, P<0.001). Awareness of PrEP was reported in 42% (very aware in 17% and slightly aware in 25%); Checkpoint participants were more aware than those from other venues (47% versus 16%, P<0.001). PrEP experience was low (1.5%); 20% expressed interest in participating in future PrEP trials. Conclusions This is the first study exploring MSM PrEP awareness in Switzerland. Although overall awareness was 42%, interest in participating in future PrEP trials was low, against high frequencies of UAI and non-serosorting. If interest in using PrEP in practice is similar, alternative measures to curb HIV transmission are required in this population.
Keywords: Pre-Exposure Prophylaxis